Diversity of cryptic Metazoa in Australian freshwaters: a new genus and two new species of sessile rotifer (Rotifera, Monogononta, Gnesiotrocha, Flosculariidae) - Segers, Hendrik; Shiel, Russell J. (Zootaxa, 2008)
Rotifers are obligate aquatic animals that are reputed to have particularly efficient mechanisms to survive extreme, or prolonged periods of drought, in the form of inconspicuously small resting stages, hidden between plant litter and sediment. In order to study this phenomenon, we conducted a hatching experiment on dry sediment from two billabongs in Victoria, Australia, which had been stored under dehydrated conditions for about one year. Here, we report on the diversity of rotifers that hatched during the experiment. A total of 48 species, a majority of which belong to groups of sessile rotifers, were recorded, including several new or interesting taxa. Two new taxa are described: Floscularia wallacei n. spec., and Pentatrocha gigantea n. gen., n. spec., the largest rotifer ever recorded. Ptygura ctenoida Koste & Tobias, 1990 is raised to species rank.